Reading and listening to the world: the writing of Andrés Sánchez Robayna before the mystical tradition (XXI Century. Spanish Literature and Culture, 2012)
Andres Sánchez Robayna takes us on a journey around the world to show us how to read the world and then how to listen to it. We follow the path of mysticism, in the footsteps of Juan de la Cruz and Teresa de Avila. And yet his poetry is very contemporary poetry since  he tries to reconcile mysticism with silence. To read this book of poetry is to seek knowledge by listening to nature. To listen to nature is to listen to unsaid words, and yet these “unsaid words” are the path to the “said words” , that is, the total knowledge which sheds light on our human existence. The circle of poems comes to a close when we  realize this journey has taken us to
Keywords: mysticism; silence; poetry; nature; Andres Sánchez Robayna